ENHANCED PERFORMANCE ON SOFTWARE DEVELOPMENT PROJECT THROUGH PROJECT PLANNING, TECHNICAL FACTORS, TEAM CAPABILITY, AND PROJECT SCOPE (CASE STUDY: IT AND PRODUCT DEVELOPMENT DIVISION AT PT. X) - Gaol, Kiki Lumban; DP, Agustinus Hariadi (Dinasti Publisher, 2021)
The research was conducted in a company who engaged in the Fintech field which is inseparable from project management activities. On its implementation there is a project completion time that exceed the specified schedule due to the limited number of human resources and also those bugs in the application generated in the project being run. This research has purposes to revealed the amount of impact from project planning to technical factors, team capabilities and project scopes also to find out the amount of impact which caused by technical factors, team capabilities and project scopes towards the performance of software development project. These research data were obtained through questionnaires that involving 63 respondents. The data analysis technique used PLS-SEM. The results from this research found that project planning had a positive and significant affect on technical factors by 60.1%, team capability by 45.5% while project scope by 57.3%. Technical factors, team capability and project scope had a positive and significant affect towards the performance of software development projects with each amount of influence, namely 39.3%, 25.6% and 31%, respectively.